Neutrophilia in the bronchoalveolar lavage fluid increases coughing during flexible fiberoptic bronchoscopy in a pediatric cohort - Danino, Laura; Stehling, Florian; Eckerland, Maximilian; Orhan, Eser; Tschiedel, Eva (Frontiers in Pediatrics, 2024)
Objective This study is an addition to the already published prospective randomized double-blinded trial by Tschiedel et al. that compared two different sedation regimes in fiberoptic flexible bronchoscopy in pediatric subjects. The objective of the presented study is to analyze the correlation between the neutrophil percentage of the bronchoalveolar lavage fluid (BALF) and coughing episodes during bronchoscopy. Methods Fifty subjects, aged 1–17 years, received flexible fiberoptic bronchoscopy under deep sedation. The BALF of 39 subjects was analyzed with reference to cytology and microbiology. Results The percentage of neutrophils from the total cell count ranged from 0% to 95.3% (median 2.7). Nineteen patients (49%) had a percentage of ≥3.0%. Pearson's correlation showed a high correlation (r = 0.529, p = 0.001) between the coughing episodes per minute and the neutrophil percentage in the BALF. Analysis of variance showed a significant difference in neutrophil percentage between the indication groups (p = 0.013). The t-test (p = 0.019) showed a significant difference between the neutrophil percentage for patients with a probable airway infection under immunosuppression (median 2.9) and patients with cystic fibrosis (median 49.6). The linear regression analysis showed a significantly stronger impact of the neutrophil percentage on coughing frequency than the sedation regime (βneutrophils = 0.526 with p = 0.001 vs. βsedation = 0.165 with p = 0.251). Conclusion When bronchoscopy is to be performed on a pediatric patient with suspected bacterial or viral infection, and therefore neutrophilic airway inflammation, coughing is to be expected.